Conserved Motifs in a Tombusvirus Polymerase Modulate Genome Replication, Subgenomic Transcription, and Amplification of Defective Interfering RNAs - Gunawardene, Chaminda D. (J Virol, 2015)
The replication of plus-strand RNA virus genomes is mediated by virally encoded RNA-dependent RNA polymerases (RdRps). We have investigated the role of the C-proximal region in the RdRp of tomato bushy stunt virus (TBSV) in mediating viral RNA synthesis. TBSV is the prototype species in the genus Tombusvirus, family Tombusviridae, and its RdRp is responsible for replicating the viral genome, transcribing two subgenomic mRNAs, and supporting replication of defective interfering RNAs. Comparative sequence analysis of the RdRps of tombusvirids identified three highly conserved motifs in their C-proximal regions, and these sequences were subsequently targeted for mutational analysis in TBSV. The results revealed that these motifs are important for (i) synthesizing viral genomic RNA and subgenomic mRNAs, (ii) facilitating plus- and/or minus-strand synthesis, and (iii) modulating trans-replication of a defective interfering RNA. These motifs were also found to be conserved in other plant viruses as well as in a fungal and insect virus. The collective findings are discussed in relation to viral RNA synthesis and taxonomy. IMPORTANCE Little is currently known about the structure and function of the viral polymerases that replicate the genomes of RNA plant viruses. Tombusviruses, the prototype of the tombusvirids, have been used as model plus-strand RNA plant viruses for understanding many of the steps in the infectious process; however, their polymerases remain poorly characterized. To help address this issue, the function of the C-terminal region of the polymerase of a tombusvirus was investigated. Three conserved motifs were identified and targeted for mutational analysis. The results revealed that these polymerase motifs are important for determining what type of viral RNA is produced, facilitating different steps in viral RNA production, and amplifying subgenomic RNA replicons. Accordingly, the C-terminal region of the tombusvirus polymerase is needed for a variety of fundamental activities. Furthermore, as these motifs are also present in distantly related viruses, the significance of these results extends beyond tombusvirids.